(untitled) (World Bulletin of Public Health, 2024)
The article provides information about the complex of works carried out on the basis of the contract concluded between the medical facilities and the service providers. In the contract, the rights and responsibilities of the parties, as well as the price and calculation procedures for the specified technical service are given